A Performance Analysis of Improved_Eclat Algorithm in Association Rule Mining - Priya, V; Murugan, S (International Journal of Computer Sciences and Engineering, 2025)
In mining frequent Itemsets, Eclat algorithm is an important one. But it has some inefficiency. We proposed an algorithm called Improved_Eclat which is a new improved eclat method with high efficiency in the searching process to reduce the running time using two dimensional pattern tree. By comparing Improved_Eclat with Eclat , Eclat-opt and Bi-Eclat, hereby it is proved that the Improved_Eclat has the highest efficiency in mining associating rules from various databases